PEDOT:PSS Film Preparation and Characterization Using Convective Deposition System Controlled by Arduino Microcontroller for Organic Photovoltaic Application - Sawitree Wongrerkdee; Mantarat Ritruksa; Saisunee Phattum; Khathawut Lohawet; Anusit Kaewprajak; Pisist Kumnorkaew; Sutthipoj Wongrerkdee (My University, 2021)
PEDOT:PSS films are prepared using convective deposition system.The convective deposition system is designed and controlled by a low-cost Arduino microcontroller.The microcontroller shows suitable potential for the system operation with good performance.Then, the system was applied to prepare PEDOT:PSS films and the prepared films are characterized.The prepared films reveal the increase in roughness and thickness for the high-velocity operation which could be occurred due to turbulent flows of PEDOT:PSS molecules.The result causes a decrease in transmittance, resistance, and water contact angle.For organic photovoltaic application, the enhanced power conversion efficiency is observed in corresponding to the increased short-circuit current density due to carrier transport efficiency improvement in organic photovoltaic devices provided by rough surfaces and thick films.The success of organic photovoltaic fabrication confirms the accepting ability of the convective deposition system controlled by Arduino microcontroller for non-vacuum thin film deposition.Thus, it should be considered as a usefulness system for thin-film based device fabrication with a low-cost operation.
Keywords: Characterization; Deposition; Arduino; solar cell performance optimization